2016
DOI: 10.3233/wor-152106
|View full text |Cite
|
Sign up to set email alerts
|

Life stories of people on sick leave from work because of mild mental illness, pain and fatigue

Abstract: Illness may develop when experiencing crises or strain over time in private situations, this in combination with expectations and requirements in working life. Not only working environments, but also the private situations, life history events, and self-esteem of individuals, should be taken into consideration in the rehabilitation program. There is a need of research on working life that support the employee's positive self-image, and on effective rehabilitation when needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We excluded 14 studies for the following reasons: it was not primary qualitative study (45), we were unable to extract a concept (46)(47)(48)(49)(50), or the study was outside our scope. For example, the findings did not distinguish chronic pain experience from other conditions (51) or from acute pain (52)(53)(54)(55), or reported mixed (56,57) or irrelevant samples (58). We included 195 reports (59-253) of 170 unique studies, exploring the experience of at least 3589 people (1002 men) with chronic pain.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 14 studies for the following reasons: it was not primary qualitative study (45), we were unable to extract a concept (46)(47)(48)(49)(50), or the study was outside our scope. For example, the findings did not distinguish chronic pain experience from other conditions (51) or from acute pain (52)(53)(54)(55), or reported mixed (56,57) or irrelevant samples (58). We included 195 reports (59-253) of 170 unique studies, exploring the experience of at least 3589 people (1002 men) with chronic pain.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of psychosocial factors in the RTW process are also demonstrated in findings that stressful family situations and a demanding work life are common experiences among long-term sick-listed individuals (Sandmark and Renstig, 2010;Frederiksen et al, 2015;Brataas and Evensen, 2016;Corbière et al, 2016). Meta-syntheses of qualitative RTW research also point to the disruption of social life during sick leave, stressful work situations, and the importance of supportive workplace for RTW, as common experiences (Froud et al, 2014;Thisted et al, 2018;Grant et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“… 23 Other studies have explored the phenomenon on a descriptive level. 24 Yet, researchers have been encouraged to go beyond description and towards interpretative engagement while performing qualitative analyses of pain. 11 In line with this approach, we sought to understand the essential meaning of sick leave due to chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that the women felt excluded and rejected,22 struggling with an invisible physical ailment 23. Other studies have explored the phenomenon on a descriptive level 24. Yet, researchers have been encouraged to go beyond description and towards interpretative engagement while performing qualitative analyses of pain 11.…”
Section: Introductionmentioning
confidence: 99%